The Challenges of Supply Chain Management (SCM)in Industrialised Building System (IBS): Case Study in Selangor - Aini, Amira Aisyah Aini; Seow, Ta Wee; Khalid, Zailawati (Research in Management of Technology and Business, 2025)
This research explores the challenges in supply chain management (SCM) within the Industrialised Building System (IBS) in Selangor, focusing on fragmentation, inefficiencies, and a shortage of skilled labour. The objective for this study is the challenges of supply chain management in IBS and the solutions of supply chain management in IBS. The disjointed nature of the IBS supply chain hampers the timely arrival of components, causing project delays and increased costs. Moreover, a lack of collaboration among construction parties worsens these inefficiencies. A quantitative research method was used, gathering data from 30 IBS suppliers through structured questionnaires. Using SPSS, the data was analysed to find the links among challenges. The results indicate that the adoption of advanced technologies like Building Information Modelling (BIM), enhanced communication among all parties, and the standardisation of IBS components can greatly improve SCM efficiency. Additionally, proactive cost management strategies and workforce training programs are crucial to tackling labour shortages and enhancing project outcomes. These actions promote better coordination, reduce delays, and optimise resource use. The study highlights that effective collaboration, bolstered by strong digital tools, can alleviate fragmentation and allow real-time material tracking. By stressing the importance of strategic SCM approaches, this research offers practical insights to address operational challenges in IBS projects. The conclusions emphasise the necessity for sustainable SCM tactics to ensure the timely delivery of high-quality components and foster the wider adoption of IBS in Selangor. Ultimately, this study aids in the evolution of a more efficient, innovative, and sustainable construction industry in Selangor and beyond.